2011
DOI: 10.1159/000327029
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Charcot-Marie-Tooth Disease in the Population of Belgrade, Serbia

Abstract: Background: The aim of this study was to determine prevalence and 15-year survival in Charcot-Marie-Tooth disease (CMT). Methods: The study covers the period from 1 January 1988 to 31 December 2007 in the territory of Belgrade. Data on a number of CMT-affected persons and their basic demographic characteristics as well as data on the disease were collected from medical records. Data on the course and outcome of the disease were obtained through direct contact with patients, their families and their physicians.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
(16 reference statements)
4
15
1
4
Order By: Relevance
“…The problem with estimating minimal prevalence in chronic disorders is to identify all the patients in the general population/geographical region. According to Mladenovic et al [15], CMT prevalence varies in different populations and different regions within countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem with estimating minimal prevalence in chronic disorders is to identify all the patients in the general population/geographical region. According to Mladenovic et al [15], CMT prevalence varies in different populations and different regions within countries.…”
Section: Discussionmentioning
confidence: 99%
“…The second study with the lowest prevalence was also a retrospective study [15], and diagnosis was confirmed only by clinical and CMT diagnosis established according to European CMT Consortium criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different epidemiologic studies vary in quality and methodology, and prevalence estimates vary greatly ranging from 9.74 to 82.25 per 100,000. Few studies were performed nationwide, and no study had used nationwide register-based data 3…”
Section: Introductionmentioning
confidence: 99%
“…The population prevalence of CMT is estimated to range from 9.7/100,000 in Serbia [13] to 82.3/100,000 in Norway [14]. Molecular diagnosis is reached in about 92% of CMT1 patients, but in only 43% of CMT2 patients [15].…”
mentioning
confidence: 99%